Հայերի ներդրումը 19-20-րդ դարերի Եգիպտոսի պետականաշինության մեջ - Ազիզյան, Խ. (ՀՀ ԳԱԱ հրատ.)
В истории Египта ХІХ-ХХ века оказались судьбоносными, поскольку именно в этот период Египет обрел независимость, избавившись от гнета Османской империи, что нашло отражение в ряде структурных реформ в государственной системе, а также преобразований в социально-экономической сфере. The 19th and 20th centuries turned out to be momentous in the history of Egypt as it was within this period that Egypt gained its independence, freeing itself from the oppression of the Ottoman Empire. The independence was reflected in a range of structural reforms in the system of the government as well as in the transformation of socio-economic sphere.
Keywords: Սփյուռք